Using anatomical traits to understand root functions across root orders of herbaceous species in a temperate steppe. Issue 2 (18th February 2022) - Zhou, Meng; Guo, Yumeng; Sheng, Jun; Yuan, Yujia; Zhang, Wen‐Hao; Bai, Wenming
Summary: Root anatomical traits play crucial roles in understanding root functions and root form–function linkages. However, the root anatomy and form–function linkages of monocotyledonous and dicotyledonous herbs remain largely unknown. We measured order‐based anatomical traits and mycorrhizal colonization rates of 32 perennial herbs of monocotyledons and dicotyledons in a temperate steppe. For monocots, relative constant proportion of cortex and mycorrhizal colonization rates, but increased cell‐wall thickening of the endodermis and proportion of stele were observed across root orders, indicating a slight reduction in absorption capacity and improvement in transportation capacity across orders. For dicots, the cortex and mycorrhizal colonization disappeared in the fourth‐order and/or fifth‐order roots, whereas the secondary vascular tissue increased markedly, suggesting significant transition of root functions from absorption to transportation across root orders. The allometric relationships between stele and cortex differed across root orders and plant groups, suggesting different strategies to coordinate the absorption and transportation functions among plant groups. In summary, our results revealed different functional transition patterns across root orders and distinct strategies for coordinating the absorption and transportation of root system between monocots and dicots. These findings will contribute to our understanding of the root form and functions in herbaceous species.